Answer to If f(x) = (x2 - 2x - 1)2/3, then f'(0) =? A) 4/3 B) 0 C) -2/3 D) -4/3 E) ... (2/3)(x 2 - 2x - 1) (-1/3) (2x)(-2) (-8x/3)(x 2 - 2x - 1) (-1/3 ...
Read more

Positive: 50 %

... If F(x) = 3x^2 - 5x and G(x) = 2x - 4, ... I'm having trouble with this problem. Any help is appreciated. ... equals 2, then g(f(2)) is the same thing ...
Read more

Positive: 47 %

More resources

then f ( x ) = ( x ) 4 ( x ) 2 = x 4 x 2 = f ( x ) if f ( x ) = x 2 + 1 , then f ( x ) = ( from V63 0123 at NYU ... This preview has blurred sections. Sign ...
Read more

Positive: 50 %

MATH 10550, EXAM 1 SOLUTIONS 1. If f(2) = 5, f(3) = 2, f(4) ... (4 x2) x2(2 + p 4 x2) ... = x4 + 6x 2. Then f( 2) = 2, f(0) = 2 and f(1) = 5. Since f(x) ...
Read more

Positive: 45 %

... (x))]' = 2(x^2 + 3x -2)*(2x+3) f'(1) = [u(v(1)] ... We know that if f(x) = u (v(x) , then. f'(x) = (u(v(x)) ' = u'(v ... = 2x^2 + 6x - 4. dt/dx = 2x ...
Read more

Positive: 31 %

Inverse Functions. An inverse function goes the other way! Let us start with an example: Here we have the function f(x) = 2x+3, written as a flow diagram:
Read more

Positive: 8 %

Show more results

f(x)= x^2 / (x-2) find f'(1) ... (x) = x^2 /(x-2) We know that if f= u/v , then f'= (u'v-uv')/v^2. ... (x(x-2) + 2(x-2)+4)/(x-2) =x +2 +4/(x-2) f'(x) = ...
Read more

Positive: 50 %

Algebra -> Equations-> SOLUTION: If f(x)=0.2x-4, then what is f^-1(x)? ... Question 672654: If f(x)=0.2x-4, then what is f^-1(x)? Answer by ReadingBoosters ...
Read more

Positive: 49 %

If f(x) = e^(tan^2)x, then f'(x)=|dw:1334602346214:dw|. is it\[\large f(x)=e^{\tan^2x}\] ... (5x^4)(x^5+7)^2 right? TuringTest; 4 years ago. ok good, ...
Read more

Positive: 44 %

If f ( x ) = 2 x 3-1 x 3 + 4 3 x-5 , then f ( x ) = ( 3 x-5 )( 6 x 2 + 3 x-4 )-( 2 x 3-x-3 + 4 ) ... then f 0 ( x ) = ( 3 x-5 )( 6 x 2 + 3 x-4 )-( 2 x 3- ...
Read more

Positive: 37 %

Section2.7 One-to-One FunctionsandTheirInverses ... Let f(x) = x2,x ≥ 2, then f−1(x) = √ x,x ≥ 4. 18. Let f(x) = x2,x < −3, then f−1(x) = ...
Read more

Positive: 27 %

If $ f(x)=x^2-3x+1$ then $ f ... $$f(x-2)=(x-2)^2-3(x-2)+1$$ $$f(x-2)=x^2-4x+4-(3x-6)+1$$ $$f(x-2)=x^2-4x+4-3x+6+1$$ $$\color{green}{\boxed{f(x-2)=x^2-7x ...
Read more

Positive: 14 %

If f(x)=1/2x-14, then f^-1(x) ... 4 Inverse Functions The function f (x) = x + 4 from the set A = {1, 2, 3, 4} to the set B = {5, 6, 7, 8} ...
Read more

Positive: 10 %

If 2^x - 2^x-2 = 3*(2)^13, What is the value of x? This is from the GMAT Prep 1. ... -If we let x equal 4, then we get (2^4) - (2^2) = (16)-(4) = 12
Read more

Positive: 10 %

... f(x)=4+x+2x^2[/math ... When X = 3, the slope of the function f(x) = 4 + x ... then the slope of the graph of the function f at x = 3 is calculated ...
Read more

Positive: 10 %

... f(1)), and then you have to find the constant of the line with the same slope so ... The function is [math]f(x) =x^3-2x^2-5x ... (x) = 3x^2 - 4^x - 5 ...
Read more

Positive: 10 %

+2 = x. 6. Let f(x) = 9x+4, then f−1(x) = 7. Let f(x) = 3 ... Let f(x) = x2,x ≥ 2. Then f−1(x) = ...
Read more

Positive: 10 %

Make f(x) =y. So you have y=2x. Now swap the x and the y. What do you have?
Read more

Read more

50 %